Maximizing SME Financial Performance: The Role of Financial Literacy, Access to Financing, and Business Strategy - Mongan, Claudio Julio; Lambe, Kristian Hoegh Pride; Irdawati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study investigates the influence of financial literacy and access to financing on the financial performance of SMEs and manufacturing companies in Makassar, Indonesia, with business strategy as a moderating variable. Using a quantitative, explanatory research design and a sample of 96 respondents, data were analyzed through Structural Equation Modeling with the SmartPLS tool. The results reveal that financial literacy does not significantly impact financial performance, suggesting that knowledge alone may not translate into better financial outcomes. Conversely, access to financing has a significant positive effect on financial performance, highlighting the critical role of financial resources in business development. Furthermore, business strategy does not moderate the relationship between financial literacy and performance but does negatively moderate the relationship between access to financing and performance. This indicates that misalignment between financing utilization and strategy may hinder financial improvements. The study contributes to understanding how internal capabilities and strategic orientation influence performance outcomes and offers practical insights for SMEs in aligning strategies with financial decisions. Future research should explore other moderating factors to deepen understanding of these dynamics.